Spirituality as a way: the wisdom of Japan - Kashio, Naoki; Becker, Carl (Kyoto University Press, 2021)
How do Japanese people foster spiritual awareness? This book provides a fresh perspective on spirituality by highlighting the wisdom of Japan: ‘Way’ (pronounced michi or do in Japanese), which makes life a place for self-cultivation and personal growth, as seen in budo (the Way of martial arts) and geido (the Way of art). Traditionally embodied in the daily lives of the Japanese people, this practical perspective covers life situations ranging from greetings and meals to lying down and sitting up. These discussions of Japanese spirituality range from grief care, spiritual care, reincarnation, Zen and meditation to philosophical worldviews. Japanese spirituality as a Way contrasts with Western spirituality that tends to be based on a cognitive approach with a background of mind-body dualism. Today, as the traditional interconnectedness of humanity is increasingly fragmented, the authors hope their contribution from Japan may promote the study, understanding, and practice of spirituality around the world.